The Frequency and Antibiotic Susceptibility Patterns of Uropathogens in a Low-Income Locality of Karachi - Jehan, Musarrat; Harani, Mahadev; Yasmin, Rizwana; Akhtar, Sahar; Masood, Saleha (International Journal of Pathology, 2018)
Objective: To assess the frequency of common organisms causing urinary tract infection and their antibiotic sensitivity patternsin a low income locality of Karachi to guide effective empirical therapy.Methodology: This prospective descriptive study was conducted during a period from January 2013 to December2013 at a teaching hospital in Karachi. A total of 970 urine samples of indoor and outdoor patients were culturedand antimicrobial sensitivity testing of all isolates were performed using commercially available disks of variouscommonly used antibiotics.Results: Our results indicated that E.coli (55.8%) was the commonest organism causing urinary tract infection inthis community. Other organisms isolated were Staphylococcus aureus, Klebsiella spp., Enterococcus spp., Serratiaspp., Enterobacter spp., Pseudomonas spp., Proteus spp., Morganella spp. and Citrobacter spp.All organisms showed better sensitivity to imipenem followed by tazobactam and amikacin. Most species showedresistance to multiple drugs including Augmentin, trimethoprim- sulfamethoxazole and the quinolone group ofantibiotics which are currently used as empirical therapy of UTI.Conclusion: E.coli is the commonest uropathogen isolated. Multidrug resistance is common among uropathogens,with high resistance against commonly used antibiotics in empirical therapy. Regular monitoring of antibioticresistance and concrete steps to decrease it, are needed for formulating effective empirical therapy.